CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

Lactose-decorated, alginate-coated chitosan nanoparticles loaded with Coomassie Brilliant Blue G-250 protect colonic barrier integrity in experimental colitis - Maha M. Amer; Ahmed Y. Kira; Sameh Saber; Abdulaziz A. Alsalloom; Mostafa M. Khodeir; Hala A. Elashry; Rabab S. Hamad; Adel Alhomaidi; Hamad Alsaykhan; Mohammed Alorini; Mohamed R. Abdel-Hamed; Huda Eltayeb; et al. (Tissue and Cell, 2026)

Maize silk-based biostimulant seed priming enhances salt resilience and productivity in Zea mays by upregulating antioxidant defenses and targeted ion-transport genes - Amany H.A. Abeed; Hesham Alharby; Eman E.E. Belal; Ibrahim A.A. Mohamed; Shaymaa A.A. Badr; Mohamed A.M. Eid; Ali A.S. Sayed; Mostafa M. Rady; Ahmed Shaaban (Plant Science, 2026)

Rosemary (Rosmarinus officinalis) Extract Attenuates Methotrexate-Induced Oxidative Stress, Inflammatory Disturbance, and Apoptotic Lung Injury: A Molecular and Histopathological Study - Abd El Ghany A. Moustafa; Aly Fahmy Mohamed; Ibrahim M. Ibrahim Amr; Hassan Fathy Kaabo; Laila El-sayed El-moselhy; Tamer Albasyoni Gomah; Amer M. Abdel Hamid; Amal Mahmoud Hammad; Walid Mostafa Sayed Ahmed; Fawzy Mahmoud Abou Galala; Fayez Mohammed Abd Elfattah Elbayoumy; Mohamed E. Amer; et al. (Cell Biochemistry and Biophysics, 2026)

Type 2 Diabetes-Induced Molecular and Functional Impairment of Adipose Tissue-Derived Mesenchymal Stromal Cells (ASCs) and Interferon Gamma Priming for Enhanced Diabetic ASC-Based Therapy - Alaa Zeinhom; Ammar Y. Mohamed; Nahla N. Abdel-Aziz; Mostafa Sayed Diab; Amir M. H. Salem; Noha N. Yassen; Eman E. A. Mohammed; Amal M. Mohamed; Ola M. Eid; Shymaa H. Hussein; Marwa Farid; Engy K. Tharwat; et al. (Stem Cell Reviews and Reports, 2026)

Thiazolidinedione-triazole hybrids: design, synthesis, and biological evaluation as dual inhibitors of α-amylase and aldose reductase with antioxidant activity for antidiabetic therapy - Eman E. Nasr; Mohamed R. Elnagar; Nahed Nasser Eid El-Sayed; Marwa I Serag; Mostafa M. Elbadawi; Adel S. El-Azab; Simone Brogi; Hazem A. Ghabbour; Abdelrahman Hamdi; Alaa A.- M. Abdel-Aziz (Molecular Diversity, 2026)

From waste to worth: A bio-inspired green route for the fabrication of yucca leaf–TiO2 nanocomposites toward efficient and sustainable water purification - Sayed Kotb Ali; Mostafa M. Emara; Rabie Saad Farag; Moaz M. Abdou; Mahmoud F. Mubarak (Environmental Nanotechnology, Monitoring & Management, 2026)

Perindopril and L‑arginine protect against arsenic trioxide–induced neurotoxicity via Keap1/Nrf2/HO‑1 activation and suppression of neuroinflammation and apoptosis - Basel A. Abdel-Wahab; Ahmed M. Abd-Eldayem; Ehab A. M. El-Shoura; Saad Misfer; Ahmed A. N. Ahmed; Eman K. Rashwan; Hend Mostafa Selim; El-sayed Gawesh; Olfat E. Mostafa; Sabrin A. Abdel Wahab; Rania A. Gad (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

New bioactive mono-acyl glycerol ester from the Red Sea marine coral Sclerophytum levi - Basma H. Farouk; Asmaa M. Abdel-Tawab; Mohamed E. Mostafa; Fawzia Z. El-Ablack; El Sayed A. E. Hamed; Seif-Eldin N. Ayyad (Natural Product Research, 2026)

Compost-mixed Biochar Improves Saline Soil Properties and Enhances Brassica Oleracea var. Capitata physio-biochemical Responses - Ahmed R. Abd EL-Tawwab; Abdelsattar Abdelkhalik; Ahmed Shaaban; Basma R. Abdel-Moatamed; Khaulood A. Hemida; Ali A.S. Sayed; Mostafa M. Rady; Hani S. Saudy; Mohammed A.H. Gyushi (Journal of Soil Science and Plant Nutrition, 2026)
The present research aimed to correlate changes in saline soil properties and cabbage agro-physiological attributes under compost-biochar co-application. The treatments used prior to cabbage cultivation were soil applications of compost/biochar mixtrure (CMB) at rates of 0 (CMB 0 ), 10 (CMB 10 ), and 20 (CMB 20 ) t ha –1 in a randomized complete block design with three replications. The CMB 20 was the effective practice for reducing dry bulk density, saturated hydraulic conductivity, pH, and electrical conductivity, while improving total porosity, water-holding pores, soil moisture at field capacity, organic matter, cation exchange capacity, and nutrient availability. CMB 20 also improved plant relative water content, membrane stability index, and chlorophyll a and b concentrations. Hydrogen peroxide and malondialdehyde decreased by 13.5% each under CMB 20 treatment. Cabbage plants grown in saline soil produced greater phenolics content (56.0%) with higher superoxide dismutase (17.2%) activity in CMB 20 -treated plots than CMB 0 . Leaf nitrogen, phosphorus, and potassium contents enhanced by 10.1, 28.1, and 18.4%, respectively, compared with CMB 0 . Finally, CMB 20 achieved the maximal improvements in leaf number plant − 1 (41.8%), leaf area plant − 1 (216.2%), above-ground biomass (174.5%), head circumference (38.2%) and marketable yield (101.6%) of cabbage. It could be concluded that amending saline soil with CMB is regarded as a promising treatment for alleviating the salinity hazards on cabbage via modulating soil properties and physiological responses. Hence, CMB application, 20 t ha –1 , can be recommended as an agronomic practice for cabbage production to obtain high yield and quality.

Ecological Risk Assessment and Environmental Status of Heavy Metals for the Bottom Sediments of Sharm El-Luli, Red Sea Coast, Egypt - Mohammed H. Aljahdali; Ramadan M. El-Kahawy; Mostafa M. Sayed; Petra Heinz; Michael Wagreich (Journal of Marine Science and Engineering, 2026)
Sharm El-Luli, one of the most pristine embayments along Egypt’s Red Sea coast, is increasingly recognized as a sensitive sink for terrigenous inputs and emerging anthropogenic pressures. This study assesses the distribution, sources, and ecological and human health implications of heavy metals in bottom sediments collected throughout the lagoon. Concentrations of Fe, Mn, Zn, Cu, Pb, Ni, Cd, and Co were quantified and assessed using a suite of geochemical indicators and environmentally based indices. Sediment quality guidelines (SQGs; TEL–PEL and ERL–ERM) were applied to evaluate potential biological effects. Most metals exhibited background to minor enrichment, although localized elevations of Pb, Ni, and Zn suggest contributions from episodic wadi runoff and limited tourism-related inputs. Igeo and CF values generally indicated low to moderate contamination, while SQG comparisons showed that exceedances of TEL values occurred primarily for Ni and Pb, implying occasional risk for benthic organisms. Multivariate statistical analysis (PCA) separated metals into two principal components: a lithogenic component dominated by Fe, Mn, and Co, reflecting the influence of Precambrian source rocks; and an anthropogenic-mixed component (Pb, Zn, Cu, Ni) associated with terrigenous pulses and local human activity. Human health risk assessment (non-carcinogenic) showed hazard index (HI) values below unity for both adults and children, indicating negligible immediate health concerns, while potential carcinogenic risk raised in adults via ingestion for Cr followed by Cd and Ni than in children. The results highlight that while Sharm El-Luli remains relatively unimpacted, the lagoon’s geomorphology and low hydrodynamic energy promote metal retention, underscoring the need for continuous monitoring as coastal use intensifies.

Oil sludge from an environmentally hazardous pollutant to an efficient source for energy production via thermal/ catalytic pyrolysis routes - Mohamed N.A. Mahmoud; Esraa M. El-Fawal; Ahmed M.A. El Naggar; Asmaa I. Zahran; Hussien A. El Sayed; Islam M. El-Sewify; Bassem H. Heakal; Mostafa M.H. Khalil (Fuel, 2026)

From Cerebrospinal Fluid to Blood Draw: Plasma p-Tau217 as a Non-Invasive Biomarker for Alzheimer’s Disease: A Fagan Nomogram-Based Meta-Analytic Study - Nesma M. Gebril; Abdelrahman M. Elettreby; Abeer H. Younis; Mostafa Hossam El Din Moawad; Afaf M. Hafez; Gamal El Sayed; Kariman M. Abdelrahman; Sarah M. El-Kot (Molecular Neurobiology, 2026)
Alzheimer’s disease (AD) is the leading cause of dementia worldwide and is pathologically defined by amyloid-β and tau accumulation. Current diagnostic methods, such as PET imaging and cerebrospinal fluid (CSF) assays, are accurate but invasive, costly, and limited in accessibility. Plasma phosphorylated tau at threonine 217 (p-tau217) has emerged as a promising blood-based biomarker, but evidence from individual studies remains heterogeneous. We conducted a systematic review and meta-analysis to evaluate the diagnostic performance of plasma p-tau217 for AD. Following PRISMA guidelines, PubMed, Scopus, and Web of Science were searched up to July 2025. Eligible studies included clinical or biomarker-defined AD cohorts that reported plasma p-tau217 accuracy against amyloid or tau positivity or clinical diagnosis. Data on sensitivity, specificity, likelihood ratios, and diagnostic odds ratio (DOR) were extracted. Study quality was assessed using QUADAS-2. Pooled estimates were calculated using a Bayesian bivariate model, and heterogeneity was explored with meta-regression and subgroup analyses. Twenty-seven studies including 19,652 participants were analyzed. Plasma p-tau217 demonstrated high diagnostic accuracy for biomarker-defined AD, with pooled sensitivity of 85.4% (95% posterior intervals [PI]: 81.4–88.7), specificity of 88.0% (95% PI: 85.1–90.6), positive likelihood ratio (PLR) 7.13, negative likelihood ratio (NLR) 0.167, and DOR 42.7. Performance was consistent across amyloid PET and CSF reference standards. Subgroup analyses showed robust accuracy for amyloid positivity (sensitivity 87.3%, specificity 85.5%), tau positivity (sensitivity 84.9%, specificity 93.8%), and clinical AD diagnosis (sensitivity 72.9%, specificity 89.5%). Plasma p-tau217 consistently outperformed other blood biomarkers and correlated with cognitive decline, frailty, and behavioral impairment. Risk of bias was generally low, with no major publication bias detected. This meta-analysis indicates that plasma p-tau217 demonstrates promising diagnostic accuracy for detecting AD pathology across biomarker-defined reference standards. However, heterogeneity across assays, populations, and reference definitions, along with the use of optimized cut-offs in some studies and the limited power of publication-bias assessments, warrant cautious interpretation. Plasma p-tau217 appears well suited as a triage biomarker to guide confirmatory testing, but further large, prospectively designed studies with standardized assays and externally validated thresholds are needed before widespread clinical implementation.

Comparative analysis of nutritional, rheological, and sensory attributes of biscuits enriched with white and black chia seed powders: Evaluation under Egyptian cultivation conditions - Clara R. Azzam; Sayed M. Mostafa; Mokhtar S. Rizk; Ramadan A. Arafa; Emad A. Salem; Ahmed M.S. Hussein (Innovative Food Science & Emerging Technologies, 2025)

State-of-the-Art Sugarcane Production in African Region - Pradeep Mishra; Mostafa Abotaleb; Binita Kumari; El-Sayed M. El-kenawy; Shikha Yadav (Sugar Tech, 2025)

Efficacy and safety of nitazoxanide and escitalopram as adjuvant therapies in patients with rheumatoid arthritis: a randomized controlled study - Tarek M. Mostafa; Abeer A. El-Sayed; Abdel Moaty A. Afifi; Dalia R. El-Afify (European Journal of Clinical Pharmacology, 2025)
Objective This research aimed at evaluating the effectiveness and safety of nitazoxanide and escitalopram as adjuvant therapies in patients with rheumatoid arthritis (RA). Methods In this randomized controlled parallel study, 90 patients with active RA were randomized into three groups; group 1 (control group; n = 30) which received traditional therapy, group 2 (Nitazoxanide group; n = 30) which received traditional therapy plus 1 gm/day oral nitazoxanide, and group 3 (Escitalopram group; n = 30) which received traditional therapy plus 10 mg/day oral escitalopram for three months. At baseline and 3 months after treatment, clinical and functional assessments were done through the 28-joint count disease activity score using C-reactive protein (DAS28-CRP), the health assessment questionnaire-disability index (HAQ-DI), and the patient’s global assessment (PGA). Also, serum levels of high-sensitivity C-reactive protein (hs-CRP), signal transducer and activator of transcription-3 (STAT-3), Janus kinase-2 (JAK-2), toll-like receptors 4 (TLR-4), interleukin-1 beta (IL-1β), and malondialdehyde (MDA) were assessed. Data were analyzed using paired t -test and one-way analysis of variance, followed by Tukey’s HDS test. Results Three months after treatment and as compared to the control group, the nitazoxanide group showed a significant decline in PGA ( P = 0.042), and serum levels of STAT-3 ( P < 0.001), JAK-2 ( P < 0.001), TLR-4 ( P < 0.001), and IL-1β ( P < 0.001). On the other hand, the escitalopram group produced a significant decrease in DAS28-CRP score ( P = 0.029), HAQ-DI score ( P = 0.001), and serum levels of JAK-2 ( P = 0.001), TLR-4 ( P < 0.001), IL-1β ( P < 0.001), and MDA ( P < 0.001). As compared to nitazoxanide group, the escitalopram group produced a significant decline in fatigue score ( P < 0.001) and serum levels of both IL-1β ( P = 0.023) and MDA ( P < 0.001). Both medications were safe; however, chromaturia was the only significant nitazoxanide-related adverse effect. Conclusion Nitazoxanide and escitalopram could serve as potential adjuvant therapies for patients with RA based on their effectiveness and safety data.

Eco-friendly solutions: a comprehensive review of natural coagulants for sustainable water treatment - Sayed Kotb Ali; Moaz M. Abdou; Mostafa M. Emara; Rabie Saad Farag; Mahmoud F. Mubarak (Environmental Geochemistry and Health, 2025)
Water pollution and scarcity are escalating global challenges that necessitate the development of sustainable water treatment technologies. Coagulation-flocculation, a crucial method for water purification, has traditionally relied on chemical coagulants such as alum and ferric chloride. However, these chemical treatments are associated with significant drawbacks, including the generation of toxic sludge, disruption of water pH, high operational costs, and adverse environmental impacts. In response to these issues, natural coagulants derived from plants, animals, and microorganisms have emerged as promising eco-friendly alternatives. This review explores the mechanisms, applications, and environmental advantages of natural coagulants in water treatment. Studies demonstrate their effectiveness in removing turbidity, heavy metals, pathogens, and other pollutants from both surface and synthetic wastewater. Compared to chemical coagulants, natural alternatives produce less sludge, are less toxic, and offer a more sustainable and environmentally friendly solution to water treatment. However, challenges persist, particularly in terms of scalability, standardization, and cost-effectiveness. The performance of natural coagulants can vary depending on geographical origin, and the lack of standardized extraction methods hinders their large-scale application. Future research should focus on optimizing extraction processes, addressing scalability issues, and exploring hybrid systems that combine the benefits of both natural and chemical coagulants. The continued development of natural coagulants holds great promise for creating more sustainable, cost-effective, and environmentally friendly water treatment solutions. Graphical Abstract

Enhanced photocatalytic performance of Ag-doped CuWO₄ thin films prepared by chemical spray pyrolysis - Mohammed M. Gomaa; Mahmoud S. Abdel-Wahed; Mostafa Boshta; Mohamed H. Sayed (Environmental Science and Pollution Research, 2025)

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

Development of novel ferrocene-functionalized NH2-MIL-125 MOF for efficient photocatalytic degradation of indigoid dyes under visible light - Mostafa A. Sayed; Osama A.S. Rafea; Ali M. Abdel-Aziz; Reda M. Abdelhameed; Ibrahim H.A. Badr (Journal of Environmental Chemical Engineering, 2025)

Biological, biochemical, hormonal effect, and histological perturbations of Procambarus clarkii (Crustacea: Cambaridae) hemolymph on Biomphalaria alexandrina snails - Salwa A. H. Hamdi; Sayed Abd El-Monem; Amina M. Ibrahim; Mona F. Fol; Nesma A. Mostafa (Aquaculture International, 2025)
Schistosomiasis is a severe illness carried by snails of the genus Biomphalaria , which have a large distribution in Egypt. Control of the intermediate host snail is critical in limiting schistosomiasis spread. On the topic of snails’ management, bioactive products extracted from aquatic invertebrates have gained more interest. Here, for the first time, the current research intended to identify the bioactive compounds present in hemolymph collected from the freshwater crayfish Procambarus clarkii and to assess its molluscidal activity against Biomphalaria alexandrina snails. Results showed that following exposure to the sub-lethal concentrations (LC 10 34.9 and LC 25 42.8 mg/l) of hemolymph, a reduction in survival and reproductive rates of B. alexandrina was detected, as well as a substantial increase in transaminases (AST and ALT) activities, while a reduction in total protein and albumin levels. Also, levels of testosterone and 17β-estradiol hormones decreased compared to the control group. Histopathological examination of the digestive gland of treated B. alexandrina displayed a shrinkage of the tubules and an increase in the inter-tubular spaces, and also, degeneration in the oocytes and spermatocytes of the hermaphrodite glands with a loss of connective tissues between the acini was observed. Thus, based on these results, a new strategy should be developed for a better use of these agents in schistosomiasis control.

Enhancing Rainfall-Runoff Simulation in Data-Poor Watersheds: Integrating Remote Sensing and Hybrid Decomposition for Hydrologic Modelling - Mostafa Riazi; Sayed M Bateni; Changhyun Jun; Aitazaz Ahsan Farooque; Khabat Khosravi; Soroush Abolfathi (Water Resources Management, 2025)

Benthic Ostracods as Indicators of Nearshore Pollution: An Example from Hurghada Bay, Red Sea Coast, Egypt - Ramadan M. El-Kahawy; Petra Heinz; Mostafa M. Sayed; Ammar Mannaa; Rabea A. Haredy; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
Twenty-nine sediment samples were collected from Hurghada Bay, a highly impacted coastal area along the Northern Red Sea of Egypt, to evaluate environmental quality and human-induced effects on benthic ostracods. As potential bioindicators, benthic ostracods are highly responsive to environmental disturbances, with pollution leading to reduced abundance, lower diversity, and increased opportunistic taxa. To investigate the link between ostracod assemblages and sediment contamination, we measured the concentrations of eight heavy metals (Cu, Cd, Zn, Pb, As, Cr, Ni, and Mn) using inductively coupled plasma–atomic emission spectrometry (ICP-AES). Multivariate statistical analyses identified three distinct ostracod assemblages distributed across three station groups with varying pollution levels. Group I, associated with offshore stations, exhibited low to moderate heavy metal (HM) concentrations and high ostracod abundance and was dominated by Moosella striata, Hiltermannicythere rubrimaris, Ruggieria danielopoli, Neonesidea schulzi, and Paranesidea fracticorallcola, where the water depth and sand content are the main controlling factors. In contrast, Group II, corresponding to stations with the highest HMs and total organic matter (TOM), was dominated by pollution-tolerant species Jugosocythereis borchersi, Cyprideis torosa, Alocopocythere reticulata, and, to a lesser extent, Ghardaglaia triebeli, with reduced ostracod density and diversity. Group III, characterized by stations influenced by the mud-controlling factor, had the lowest HMs and was dominated by pollution-sensitive species Xestoleberis rhomboidei, Paranesidea fortificata, and Loxocorniculum ghardaquensis. These findings highlight the ecological risks posed by HM pollution and emphasize the urgent need for pollution mitigation strategies and continued monitoring to preserve the Red Sea’s benthic biodiversity.

Quaternary ammonium compounds in medicinal herbs and health risk assessment - Yasmin S. Nasr; Osama El-Sayed Hussein; Hassan A. El-Gammal; Mostafa M. H. Khalil (Food Additives & Contaminants Part B-Surveillance, 2025)

Targeting TLR4/NF-κB signaling, oxidative stress, and apoptosis by farnesol mitigates cadmium-induced testicular toxicity in rats - Emad H.M. Hassanein; Mohammed F. Alotaibi; Reem S. Alruhaimi; Mostafa Sabry; Ghadir A. Sayed; Ahmed M. Atwa; Ayman M. Mahmoud (Tissue and Cell, 2025)

Realistic and effective degradation of petroleum related contaminants in seawater using ecofriendly NiO and ZnO nanocomposites with ca-MCM-41: Assessment and remediation - Mashael D. Alqahtani; Alshaima Sayed; May N. Bin Jumah; Nahaa M. Alotaibi; Hassan A. Rudayni; Ahmed A. Allam; Mostafa R. Abukhadra (Journal of Water Process Engineering, 2025)

Human Defensins: Structure, Function, and Potential as Therapeutic Antimicrobial Agents with Highlights Against SARS CoV-2 - Maryam Nagib; Ahmed M. Sayed; Ahmed H. Korany; Karim Abdelkader; Falah H. Shari; William G. Mackay; Mostafa E. Rateb (Probiotics and Antimicrobial Proteins, 2025)
The human defensins are a group of cationic antimicrobial peptides that range in size from 2 to 5 kDa and share a common structural motif of six disulphide-linked cysteines. Several naturally occurring human α- and β-defensins have been identified over the past two decades. They have a wide variety of antimicrobial effects, and their potential to avoid the development of resistance to antimicrobial treatment makes them attractive as therapeutic agents. Human defensins have recently been the focus of medical and molecular biology studies due to their promising application in medicine and the pharmaceutical industry. This work aims to provide a comprehensive summary of the current developments of human defensins, including their identification, categorization, molecular features, expression, modes of action, and potential application in medical settings. Current obstacles and future opportunities for using human defensins are also covered. Furthermore, we shed light on the potential of this class as an antiviral agent, particularly against SARS CoV-2, by providing an in silico-based investigation of their plausible mechanisms of action.

MircoRNAs predict and modulate responses to chemotherapy in leukemic patients - Doha El-Sayed Ellakwa; Mohamed Ahmed Abdelmalek; Mostafa M. Mostafa; Takwa E. Ellakwa; Al-Hassan Soliman Wadan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Ostracod and foraminiferal assemblages in Tébessa (Northeast Algeria): Insights into Santonian cooling effects - Sakina Nemouchi; Sihem Salmi-Laouar; Ahmed Awad Abdelhady; Amor Deghaichia; Mostafa M. Sayed; Youssef Bazeen; Michael Hesemann; Mohamed Ahmed; Mabrouk Boughdiri (Marine Micropaleontology, 2025)

Decorin alleviates non-alcoholic fatty liver disease in rats with polycystic ovary syndrome - Hany A. Elkattawy; Amira Ebrahim Alsemeh; Lashin Saad Ali; Mona Mostafa Ahmed; Asmaa Monir Eltaweel; Farha M. Shaikh; Ahmed Behiry; Ahmed El-Sayed Hassan; Deema Kamal Sabir; Dalia Mahmoud Abdelmonem Elsherbini; Sahar K. Ali; Madaniah Omar Zakari; et al. (Tissue and Cell, 2025)

Acetamiprid-induced pulmonary toxicity via oxidative stress, epithelial-mesenchymal transition, apoptosis, and extracellular matrix accumulation in human lung epithelial cells and fibroblasts: Protective role of heat-killed Lactobacilli - Samah S. Arafa; Heba A. Elnoury; Sahar Badr El-Din; Mohamed A. Sakr; Fatma Fawzi Hendawi; Rehab Ali Elsayed Masoud; Samia Soliman Barghash; Doaa Sabry Elbehairy; Ayat Abdelaty Hemeda; Islam Mostafa Farrag; Doaa Sayed Abdelrahman; Amira Mohammad Elsadek; et al. (Food and Chemical Toxicology, 2025)

Efficacy of Aster chinensis aerial parts metabolites in BALB/c mice model of Imiquimod-induced psoriasis skin inflammation - Mai S. Hendawy; Mona M. Hashem; Ahmed A. Zaki; Mostafa A. Rabie; Nesrine S. El Sayed; Riham Salah El Dine; Ali M. El-Halawany (Inflammopharmacology, 2025)
Using a bioassay-guided fractionation approach, the most potent anti-psoriatic components of Aster squamatus herb, Aster chinensis stalks, and Aster chinensis flowers, cultivated in Egypt, were identified and evaluated against Imiquimod (IMQ)-induced psoriasis in female BALB/c mice and compared to standard drug, mometasone. The topical application of A. chinensis stalk methanolic extract exhibited the strongest anti-psoriatic effects against IMQ-induced psoriasis model, as evidenced by improvements in psoriasis area severity index (PASI) score, histopathological analysis, and spleen index. Further fractionation of A. chinensis stalk methanolic extract using petroleum ether, methylene chloride, ethyl acetate, and n -butanol revealed that the methylene chloride fraction (MCF) was the most potent. Indeed, MCF significantly reduced the PASI score, alleviated histopathological changes, and restored spleen index. Mechanistically, MCF exerted its anti-psoriatic effects by suppressing inflammation, evidenced by decreased TLR-4 gene expression and lower levels of HMGB1 and NFκBp65 protein contents. Additionally, MCF reduced serum levels of pro-inflammatory cytokines interleukin (IL)-1β, IL-6, IL-23, and IL-17 while mitigating oxidative stress through increased superoxide dismutase (SOD) activity and reduced malondialdehyde (MDA) content. Notably, the efficacy of MCF was comparable to that of mometasone, with no significant differences observed. In parallel, the chemical profile of the MCF was analyzed using UHPLC-MS/MS techniques in negative and positive ionization full scan modes. MCF of A. chinensis stalk could be used a potential therapeutic agent for psoriasis.

Paleobiodiversity, Paleobiogeography, and Paleoenvironments of the Middle–Upper Eocene Benthic Foraminifera in the Fayum Area, Western Desert, Egypt - Mostafa M. Sayed; Petra Heinz; Ibrahim M. Abd El-Gaied; Ramadan M. El-Kahawy; Dina M. Sayed; Yasser F. Salama; Mansour H. Al-Hashim; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
The middle–upper Eocene successions of northwest Fayum, Egypt, provide a crucial archive for reconstructing paleoenvironmental conditions and paleobiogeographical patterns of the southern Tethys realm. Stratigraphically, the investigated section is subdivided into three rock units: the Gehannam Formation (Bartonian-Priabonian), the Birket Qarun Formation, and the Qasr El Sagha Formation (Priabonian). A total of 101 benthic foraminiferal taxa, representing 31 genera, 23 families, 13 superfamilies, and four suborders, were identified. The middle–late Eocene age is primarily determined by the co-occurrence of index spinose planktonic foraminifera (Acarinina spp., Morozovelloides spp., and Globigerinatheka semiinvoluta) and benthic foraminiferal assemblages, further supported by the presence of the nannofossil marker Chiasmolithus oamaruensis. Four local benthic biozones are identified and correlated with coeval zones in nearby areas. Quantitative analyses of benthic foraminiferal individuals, diversity indices, ecological parameters, and the benthic foraminiferal oxygen index (BFOI) reveal distinct environmental shifts. The rock unit occupied by the late middle Eocene assemblages is diversified and dominated by calcareous infaunal taxa (e.g., Bolivina spp., Fursenkoina spp., and Nonionella spp.), indicative of low-oxygen outer neritic conditions associated with elevated organic influx. In contrast, the late Eocene Birket Qarun and Qasr El Sagha showed an increase in epifaunal forms and reduced diversity, suggesting a transition to dysoxic-oxic conditions. Paleobiogeographical analysis indicates a strong affinity with the Tethyan realm, with potential faunal exchange through the Trans-Saharan Seaway. These findings enhance our understanding of Paleogene marine connections between the Tethyan and Indo-Pacific realms, contributing to broader discussions on Eocene paleobiogeography and depositional dynamics in North Africa.

Comparative Neuroprotective Potential of Nanoformulated and Free Resveratrol Against Cuprizone-Induced Demyelination in Rats - Sara A. M. El-Sayed; Ghadha Ibrahim Fouad; Maha Z. Rizk; Hanan H. Beherei; Mostafa Mabrouk (Molecular Neurobiology, 2025)
Demyelination is a frequent yet crippling neurological disease associated with multiple sclerosis (MS). The cuprizone (CZ) model, which causes demyelination through oxidative stress and neuroinflammation, is a popular tool used by researchers to examine this process. The polyphenol resveratrol (RESV) has become a promising neuroprotective agent in seeking for efficient therapies. In a rat model given CZ, we created and examined iron oxide nanoparticles (IONPs) loaded with RESV (IONP-RESV) to see how effective they were as a therapeutic agent against free RESV. According to molecular mechanisms, exposure to CZ resulted in a marked downregulation of myelin proteolipid protein (PLP) expression and an overexpression of the inflammatory markers tumor necrosis factor-α (TNF-α) and S100β, which are indicators of demyelination and neuroinflammation. It is remarkable that these CZ-induced alterations could be reversed by therapy with either RESV or IONP-RESV. Interestingly, IONP-RESV showed even stronger anti-inflammatory activity, as shown by a more noticeable downregulation of TNF-α and S100β expression. These results were confirmed by histopathological examination of the cerebral cortices. Our findings support the better neuroprotective benefits of RESV-loaded IONPs over free RESV in reducing demyelination and neuroinflammation brought on by CZ. Owing to their pro-remyelinating, anti-inflammatory, and antioxidant properties, RESV-loaded IONPs show promise as a neurotherapeutic intervention in the future for neurological diseases such as multiple sclerosis. Graphical Abstract

Purification and Immobilization of Burkholderia gladioli Cholesterol Oxidase on Calcium Alginate, with Robust Catalytic Stability for Cholesterol Oxidation In Vitro - Ashraf S. A. El-Sayed; Ahmed A. Shindia; Walaa M. El-Badry; Ahmed A. Mostafa; Abdullah A.Al-Ghanayem; Amgad M. Rady (Current Microbiology, 2025)

Renoprotective effect of berberine in cisplatin-induced acute kidney injury: Role of Klotho and the AMPK/mtor/ULK1/Beclin-1 pathway - Tasneem M. Salah; Mostafa A. Rabie; Nesrine S. El Sayed (Food and Chemical Toxicology, 2025)

Berberine-loaded iron oxide nanoparticles alleviate cuprizone-induced astrocytic reactivity in a rat model of multiple sclerosis - Ghadha Ibrahim Fouad; Mostafa Mabrouk; Sara A. M. El-Sayed; Mohamed F. Abdelhameed; Maha Z. Rizk; Hanan H. Beherei (BioMetals, 2025)
Berberine (BBN) is a naturally occurring alkaloid as a secondary metabolite in many plants and exhibits several benefits including neuroprotective activities. However, data on the neuromodulating potential of nanoformulated BBN are still lacking. In the present study, BBN loaded within iron oxide nanoparticles (BBN-IONP) were prepared and characterized by transmission electron microscopy FTIR, X-ray photoelectron spectroscopy particle-size distribution, zeta potential, and HPLC. The remyelinating neuroprotective potential of BBN-IONP relative to free BBN was evaluated against cuprizone (CPZ)-induced neurotoxicity (rats administered 0.2% CPZ powder (w/w) for five weeks). CPZ rats were treated with either free BBN or IONP-BBN (50 mg/kg/day, orally) for 14 days. Cognitive function was estimated using Y-maze. Biochemically, total antioxidant capacity lipid peroxides and reduced glutathione in the brain tissue, as well as, serum interferon-gamma levels were estimated. Moreover, the genetic expression contents of myelin basic protein Matrix metallopeptidase-9 Tumor necrosis factor-α (TNF-α), and S100β were measured. The histopathological patterns and immunohistochemical assessment of Glial Fibrillary Acidic Protein in both cerebral cortex and hippocampus CA1 regions were investigated. CPZ-rats treated with either free BBN or IONP-BBN demonstrated memory restoring, anti-oxidative, anti-inflammatory, anti-astrocytic, and remyelinating activities. Comparing free BBN with IONP-BBN revealed that the latter altered the neuromodulating activities of BBN, showing superior neuroprotective activities of IONP-BBN relative to BBN. In conclusion, both forms of BBN possess neuroprotective potential. However, the use of IONPs for brain delivery and the safety of these nano-based forms need further investigation.

Enhanced simultaneous voltammetric detection of lead, copper, and mercury using a MIL-101(Cr)-(COOH)2@MWCNTs modified glassy carbon electrode - Osama A.S. Rafea; Ali M. Abdel-Aziz; Mostafa A. Sayed; Reda M. Abdelhameed; Ibrahim H.A. Badr (Analytica Chimica Acta, 2025)

UV-A-induced oxidative stress and immunotoxicity in African catfish (Clarias gariepinus): the bioremediation potential of Spirulina platensis for aquaculture - Mohamed Hamed; Carlos E. Monteiro; Rashad E. M. Said; Mostafa A. Abdel-Maksoud; Taghreed N. Almanaa; Mervat Naguib; Hanem S. Abdel-Tawab; Alaa Osman; Jae-Seong Lee; Alaa El-Din H. Sayed (Aquaculture International, 2025)

As nature's allies: Bee honey outperforms pomegranate and lemon juices in improving physio-biochemistry, antioxidants, RubisCO gene expression, and vase life of Calendula officinalis - Mostafa M. Rady; Marwa S.M. Habib; Ibrahim A.A. Mohamed; Hesham F. Alharby; Taia A.Abd El-Mageed; El‑Sayed M. Desoky; Alaa I.B. Abou-Sreea; Esmat F. Ali (South African Journal of Botany, 2024)

Impacts of climate change and black sand on Red Sea, Egypt. A comprehensive review - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Mohamed Abd El-Aal; Sobhi M. Ghoneim; Mohsen Y. Omer; Hamdy A.M. Soliman; Eman Saad; Zeinab Bakr; Jae-Seong Lee; Alaa El-Din H. Sayed (Regional Studies in Marine Science, 2024)

Patterns distribution, concentrations and sources of radioactive elements from black sand in the Red Sea coast, Egypt - Mohamed Hamed; Mostafa A. Khaled; Rashad E.M. Said; Sobhi M. Ghoneim; Eman Saad; Mohamed Abd El-Aal; Alaa El-Din H. Sayed (Journal of Hazardous Materials, 2024)

Novel post-heat treatment green biodegradable PLA@SiO2 nanocomposite membrane for water desalination - Mostafa M. Sayed; Hamouda M. Mousa; Ahmed H. El-Shazly; Abdelrahman Zkria; Tsuyoshi Yoshitake; Marwa ElKady (Journal of Environmental Chemical Engineering, 2024)

Global Potato Production Forecasting Based on Time Series Analysis and Advanced Waterwheel Plant Optimization Algorithm - Amel Ali Alhussan; Doaa Sami Khafaga; Mostafa Abotaleb; Pradeep Mishra; El-Sayed M. El-Kenawy (Potato Research, 2024)

Forecasting Production of Potato for a Sustainable Future: Global Market Analysis - Pradeep Mishra; Amel Ali Alhussan; Doaa Sami Khafaga; Priyanka Lal; Soumik Ray; Mostafa Abotaleb; Khder Alakkari; Marwa M. Eid; El-Sayed M. El-kenawy (Potato Research, 2024)

Retraction Note: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s Disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2024)

Soil–plant Integrative Supplementation with Humic Acid and Antioxidants Improves Growth, Fruit Quality, and Antioxidant Capacity of Cd-stressed Solanum Melongena - Ali A. S. Sayed; Zahra Seoudi; Ashraf Sh. Osman; Wael M. Semida; Mostafa M. Rady; Amr Elkelish; Amr E. M. Mahmoud (Journal of Soil Science and Plant Nutrition, 2024)

Biosynthesis of Silver, Copper, and Their Bi-metallic Combination of Nanocomposites by Staphylococcus aureus: Their Antimicrobial, Anticancer Activity, and Cytotoxicity Effect - Mohsen A. Sayed; Tahany M. A. Abd El-Rahman; H. K. Abdelsalam; Sayed M. S. Abo El-Souad; Rawan Muhammad Shady; Radwa Abdallnasser Amen; Mostafa Ahmed Zaki; Martina Mohsen; Sara Desouky; Samar Saeed; Seif Omar; Asmaa A. H. El-Bassuony (Indian Journal of Microbiology, 2024)
The present study outlines an easy, cheap, and environmentally friendly way to make Staphylococcus aureus -mediated bimetallic silver-copper nanocomposites (Ag/Cu) that can fight cancer and germs. The gram-positive S. aureus synthesized Ag, Cu, and their bi-metallic nanocomposites extracellularly. We aimed to prepare the bimetallic nanocomposite in two different ways, and we compared them in terms of characterization and biological applications. The first one is a bimetallic nanocomposite (Ag/Cu b ) that was made by mixing Ag and Cu metal ions in equal amounts (50:50). Then, the whole mixture was reduced. The second is the after-reduction bimetallic nanocomposite (Ag/Cu a ), in which each metal ion was reduced separately, and then the nanocomposites were mixed (50:50%) during biological applications. Nanocomposites were characterized using UV–visible spectrophotometry, Fourier-transform infrared spectroscopy, dynamic light scattering, and transmission electron microscopy. The results demonstrated that surface plasmon bands were at 320 nm for Ag NPs and 525 nm for Cu NPs, and a shift from these peaks was observed at 290 nm in the Ag/Cu b bimetallic nanocomposite. The synthesized nanocomposites were confirmed to be in the nanoscale with 20, 40, and 80 nm spherical crystals, respectively. Nanocomposites were assayed for their antimicrobial activity against the gram-negative Pseudomonas aeruginosa , the acid-fast Mycobacterium smegmatis , the gram-positive Bacillus cereus, and S. aureus, in addition to three fungal species, which were Aspergillus flavus , A. fumigatus, and Candida albicans . The minimum inhibitory concentration and minimum bactericidal concentration were determined. The Ag/Cua/Cuaetallic nanocomposite was the most potent antimicrobial compound. The anticancer activity of the tested compounds was assayed against the hepatocellular carcinoma cell line (HepG-2). Low cytotoxic activity was recorded in most assayed nanocomposites against the baby hamster kidney cell line (BHK).

Towards the preparation of sustainable superplasticizers for geopolymeric pastes via radiation-induced grafting of sulfonic group-bearing monomers onto corn starch - Noha M. Deghiedy; Safaa M.A. El-Gamal; Mohamed Ramadan; Alaa Mohsen; Mahmoud M. Hazem; Mostafa A. Sayed; Fatma M. Helmy; Mona M. Wetwet; Ahmed E. Swilem (Carbohydrate Polymers, 2024)

Carbonate reservoir characterization and permeability modeling using Machine Learning ـــ a study from Ras Fanar field, Gulf of Suez, Egypt - Mostafa S. Khalid; Ahmed S. Mansour; Saad El-Din M. Desouky; Walaa S. M. Afify; Sayed F. Ahmed; Osama M. Elnaggar (Earth Science Informatics, 2024)
Predicting facies and petrophysical properties along and between wells is challenging in carbonate reservoir modeling. In the Nullipore carbonate reservoir, Ras Fanar field, depositional and long-term diagenetic processes result in a high degree of heterogeneity and complex distribution of facies, which in turn affect the reservoir quality. This provides a significant obstacle to building accurate geological models. This study integrates thin sections, routine core analyses, and well logging data to overcome such difficulties and model the Nullipore carbonate facies and permeability. The detailed petrographic analysis revealed the existence of seven microfacies in the reservoir, which are summed up into three facies associations (FAs), each of which represents a specific reservoir rock type (RRT): (1) supratidal FA, (2) intertidal FA, and (3) shallow subtidal FA. The three FAs were correlated with the gamma-ray logs to create facies logs for the studied wells, which were further populated via the Truncated Gaussian Simulation method. Cross-validation was used to evaluate the model's accuracy. The analysis of the available core data infers that the three RRTs are prospective and have a wide permeability distribution. However, RRT3 constitutes the best reservoir quality. The sedimentological analysis revealed that the long-term diagenetic events, involving the dolomitization of limestone and the dissolution of allochems have a major role in improving the pore connectivity and permeability of the reservoir. Fracture characterization discloses that fractures play a significant role in fluid storage and migration. Three Machine Learning (ML) models, including Adaptive boosting (AdaBoost), Gradient Boosting (GB), and Extreme Gradient Boosting (XGB), were developed to integrate the RRTs, porosity, and permeability to improve permeability prediction. Statistical analysis revealed that the XGB model outperforms other models and exhibits the highest prediction performance. The present study provides further insights into the characterization and modeling of facies and permeability of complex carbonate reservoirs. It can be applied in similar geological settings to better interpretation of depositional and diagenetic controls on reservoir quality assessment and aid in the field development plan.

Biodegradation and antimicrobial capability-induced heavy metal resistance of the marine-derived actinomycetes Nocardia harenae JJB5 and Amycolatopsis marina JJB11 - Mohamed H. El-Sayed; Muaz M. Abdellatif; Howayada M. Mostafa; Islam A. Elsehemy; Abd El-Nasser A. Kobisi (World Journal of Microbiology and Biotechnology, 2024)

Developing green slag/bentonite-based geopolymers modified with meso-porous tungsten oxide: Zeolitic phases, mechanical performance and gamma-radiation mitigation - M. Ramadan; S.M.A. El-Gamal; Mona M. Wetwet; Mostafa A. Sayed; M.M. Hazem; Noha M. Deghiedy; Ahmed E. Swilem; Alaa Mohsen (Applied Clay Science, 2024)

Optimizing Potato Disease Classification Using a Metaheuristics Algorithm for Deep Learning: A Novel Approach for Sustainable Agriculture - El-Sayed M. El-Kenawy; Amel Ali Alhussan; Doaa Sami Khafaga; Mostafa Abotaleb; Pradeep Mishra; Reham Arnous; Marwa M. Eid (Potato Research, 2024)

Occurrence, distribution, and composition of black sand along the Red Sea, Egypt - Mohamed Hamed; Mohamed Abd El-Aal; Mostafa A. Khaled; Sobhi M. Ghoneim; Eman Saad; Jae-Seong Lee; Alaa El-Din H. Sayed (Science of The Total Environment, 2024)

Neuroprotective effect of curcumin against experimental autoimmune encephalomyelitis-induced cognitive and physical impairments in mice: an insight into the role of the AMPK/SIRT1 pathway - Mohamed A. Sadek; Mostafa A. Rabie; Nesrine S. El Sayed; Helmy M. Sayed; Esraa A. Kandil (Inflammopharmacology, 2024)
Multiple sclerosis (MS) is an incurable chronic neurodegenerative disease where autoimmunity, oxidative stress, and neuroinflammation collaboration predispose myelin sheath destruction. Interestingly, curcumin, a natural polyphenol, showed a neuroprotective effect in numerous neurodegenerative diseases, including MS. Nevertheless, the influence of curcumin against MS-induced cognitive impairment is still vague. Hence, we induced experimental autoimmune encephalomyelitis (EAE) in mice using spinal cord homogenate (SCH) and complete Freund’s adjuvant, which eventually mimic MS. This study aimed not only to evaluate curcumin efficacy against EAE-induced cognitive and motor dysfunction, but also to explore a novel mechanism of action, by which curcumin exerts its beneficial effects in MS. Curcumin (200 mg/kg/day) efficacy was evaluated by behavioral tests, histopathological examination, and biochemical tests. Concisely, curcumin amended EAE-induced cognitive and motor impairments, as demonstrated by the behavioral tests and histopathological examination of the hippocampus. Interestingly, curcumin activated the adenosine monophosphate (AMP)-activated protein kinase/silent mating type information regulation 2 homolog 1 (AMPK/SIRT1) axis, which triggered cyclic AMP response element-binding protein/brain-derived neurotrophic factor/myelin basic protein (CREB/BDNF/MBP) pathway, hindering demyelination of the corpus callosum. Furthermore, AMPK/SIRT1 activation augmented nuclear factor erythroid 2-related factor 2 (Nrf2), a powerful antioxidant, amending EAE-induced oxidative stress. Additionally, curcumin abolished EAE-induced neuroinflammation by inhibiting Janus kinase 2 /signal transducers and activators of transcription 3 (JAK2/STAT3) axis, by various pathways, including AMPK/SIRT1 activation. JAK2/STAT3 inhibition halts inflammatory cytokines synthesis. In conclusion, curcumin’s neuroprotective effect in EAE is controlled, at least in part, by AMPK/SIRT1 activation, which ultimately minimizes EAE-induced neuronal demyelination, oxidative stress, and neuroinflammation. Graphical Abstract Graphical illustration of putative molecular pathways implicated in the management of EAE by curcumin. Curcumin activates AMPK/SIRT1, which in turn activates multiple pathways that hinder neurodegeneration, oxidative stress, and neuroinflammation. Moreover, curcumin conquers the inflammatory pathway JAK2/STAT3/NF-kβ.

Engineered eco-friendly composite membranes with superhydrophobic/hydrophilic dual-layer for DCMD system - Mostafa M. Sayed; H. Noby; Abdelrahman Zkria; Hamouda M. Mousa; Tsuyoshi Yoshitake; Marwa ElKady (Chemosphere, 2024)

A hybrid deep learning model for rainfall in the wetlands of southern Iraq - Fehaid Alqahtani; Mostafa Abotaleb; Alhumaima Ali Subhi; El-Sayed M. El-Kenawy; Abdelaziz A. Abdelhamid; Khder Alakkari; Amr Badr; H. K. Al-Mahdawi; Abdelhameed Ibrahim; Ammar Kadi (Modeling Earth Systems and Environment, 2023)

Highly effective direct decomposition of organic pollutants via Ag–Zn co-doped In2S3/rGO photocatalyst - Salh Alhammadi; Abdelrahman M. Rabie; Mostafa S. Sayed; Dohyung Kang; Jae-Jin Shim; Woo Kyoung Kim (Chemosphere, 2023)

Citrate-containing lemon juice, as an organic substitute for chemical citric acid, proactively improves photosynthesis, antioxidant capacity, and enzyme gene expression in cadmium-exposed Phaseolus vulgaris - Mostafa M. Rady; Hesham F. Alharby; El-Sayed M. Desoky; Ahmed R.M. Maray; Ibrahim A.A. Mohamed; Saad M. Howladar; Yasmine H. Abd Elmohsen; Ahmad Faraz; Shafaqat Ali; Abdelsattar AbdelKhalik (South African Journal of Botany, 2023)

Simvastatin attenuates aluminium chloride-induced neurobehavioral impairments through activation of TGF-β1/ SMAD2 and GSK3β/β-catenin signalling pathways - Mangreed M. Atef; Yasser M. Mostafa; Amal A.M. Ahmed; Norhan M. El-Sayed (Environmental Toxicology and Pharmacology, 2023)

Correction: Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. Khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2023)

Spirulina platensis extract improves the production and defenses of the common bean grown in a heavy metals-contaminated saline soil - Mostafa M. Rady; Ahmed S. Elrys; Eman Selem; Ahmed A.A. Mohsen; Safaa M.A.I. Arnaout; Ahmed H. El-Sappah; Khaled A. El-Tarabily; El-Sayed M. Desoky (Journal of Environmental Sciences, 2023)

Synergistic effects of graphene oxide grafted with barbituric acid nanocomposite for removal of heavy metals from aqueous solution - Mostafa M. Abdel Wahab; Galal H. Sayed; Ramadan M. Ramadan; Amr H. Mady; Abdelrahman M. Rabie; Ahmed A. Farag; Nabel A. Negm; Eslam A. Mohamed (Nanotechnology for Environmental Engineering, 2023)

Enhancing flood susceptibility modeling using multi-temporal SAR images, CHIRPS data, and hybrid machine learning algorithms - Mostafa Riazi; Khabat Khosravi; Kaka Shahedi; Sajjad Ahmad; Changhyun Jun; Sayed M. Bateni; Nerantzis Kazakis (Science of The Total Environment, 2023)

Synergistic effect of trans-zeatin and silymarin on mitigation of cadmium stress in chili pepper through modulating the activity of antioxidant enzymes and gene expressions - Mostafa M. Rady; Khalid S. Alshallash; El-Sayed M. Desoky; Hanan A.A. Taie; Ibrahim A.A. Mohamed; Ali M. El-Badri; Saad M. Howladar; Abdelsattar AbdelKhalik (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Interactive adverse effects of low-density polyethylene microplastics on marine microalga Chaetoceros calcitrans - Hoda H. Senousy; Hanan M. Khairy; Heba S. El-Sayed; Eman R. Sallam; Mohamed A. El-Sheikh; Mostafa E. Elshobary (Chemosphere, 2023)

UPLC-MS/MS and GC-MS based metabolites profiling of Moringa oleifera seed with its anti- Helicobacter pylori and anti-inflammatory activities - Abeer M. El Sayed; Farghaly A. Omar; Marwa Mostafa Abdel-Aziz Emam; Mohamed A. Farag (Natural Product Research, 2022)

Irisin improves adiposity and exercise tolerance in a rat model of postmenopausal obesity through enhancing adipo-myocyte thermogenesis - Rehab E. Abo El Gheit; Reham L. Younis; Mervat H. El-Saka; Marwa N. Emam; Nema A. Soliman; Rehab M. El-Sayed; Yasser Mostafa Hafez; Norhan Ahmed AbuoHashish; Doaa A. Radwan; Howayda E. khaled; Samar Kamel; Sawsan A. Zaitone; et al. (Journal of Physiology and Biochemistry, 2022)
The prevalence of obesity and its associated metabolic disorders, along with their healthcare costs, is rising exponentially. Irisin, an adipomyokine, may serve as a critical cross-organ messenger, linking skeletal muscle with adipose tissue and the liver to integrate the energy homeostasis under diet-induced obesity. We aimed to explore the putative role of irisin in the protection against obesity in a postmenopausal rat model by modulating energy expenditure (EE). Bilateral ovariectomy (OVX) was performed. After 3 weeks of recovery, the OVX rats were classified according to their dietary protocol into rats maintained on normal diets (ND) (OVX) or high-fat diet (HFD) groups. The HFD-fed animals were equally divided into OVX/HFD, or irisin-treated OVX/HFD groups. Sham rats, maintained on ND, were selected as the control group. We evaluated anthropometric, EE, and molecular biomarkers of browning and thermogenesis in inguinal white adipose tissue and skeletal muscle, and the activity of the proteins related to mitochondrial long chain fatty acid transport, oxidation, and glycolysis. HFD of OVX further deteriorated the disturbed glucose homeostasis, lipid profile, and the reduced irisin, thermogenic parameters in adipose tissue and skeletal muscle, and EE. Irisin treatment improved the lipid profile and insulin resistance. That was associated with reduced hepatic gluconeogenic enzyme activities and restored hepatic glycogen content. Irisin reduced ectopic lipid infiltration. Irisin augmented EE by activating non-shivering thermogenesis in muscle and adipose tissues and decreasing metabolic efficiency. Our experimental evidence suggests irisin’s use as a potential thermogenic agent, therapeutically targeting obesity in postmenopausal patients. Graphical abstract Irisin modulates the non-shivering thermogenesis in skeletal muscle and adipose tissue in postmenopausal model

Neuroprotective Potential of Intranasally Delivered Sulforaphane-Loaded Iron Oxide Nanoparticles Against Cisplatin-Induced Neurotoxicity - Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Mostafa Mabrouk; Kawkab A. Ahmed; Hanan H. Beherei (Neurotoxicity Research, 2022)
Cisplatin (CIS) is a platinum-based chemotherapeutic drug that is widely used to treat cancer. However, its therapeutic efficiency is limited due to its potential to provoke neurotoxicity. Sulforaphane (SF) is a natural phytochemical that demonstrated several protective activities. Iron oxide nanoparticles (Fe 3 O 4 -NPs) could be used as drug carriers. This study aimed to explore the nanotoxic influence of SF-loaded within Fe 3 O 4 -NPs (N.SF), and to compare the neuroprotective potential of both N.SF and SF against CIS-induced neurotoxicity. N.SF or SF was administrated intranasally for 5 days before and 3 days after a single dose of CIS (12 mg/kg/week, i.p.) on the 6 th day. Neuromuscular coordination was assessed using hanging wire and tail-flick tests. Acetylcholinesterase (AChE) activities and markers of oxidative stress were measured in the brain. In addition, the brain iron (Fe) content was estimated. CIS significantly induced a significant increase in AChE activities and lipid peroxides, and a significant decrement in glutathione (GSH) and nitric oxide (NO) contents. CIS elicited impaired neuromuscular function and thermal hyperalgesia. CIS-induced brains displayed a significant reduction in Fe content. Histopathological examination of different brain regions supported the biochemical and behavioral results. Contradict, treatment of CIS-rats with either N.SF or SF significantly decreased AChE activity, mitigated oxidative stress, and ameliorated the behavioral outcome. The histopathological features supported our results. Collectively, N.SF demonstrated superior neuroprotective activities on the behavioral, biochemical, and histopathological (striatum and cerebral cortex) aspects. N.SF could be regarded as a promising “pre-clinical” neuroprotective agent. Furthermore, this study confirmed the safe toxicological profile of Fe 3 O 4 -NPs.

Combined Effect of Prickly Pear Waste Biochar and Azolla on Soil Fertility, Growth, and Yield of Roselle (Hibiscus sabdariffa L.) Plants - Hassan M. Al-Sayed; Ahmed M. Ali; Mahmoud A. Mohamed; Mostafa F. Ibrahim (Journal of Soil Science and Plant Nutrition, 2022)
Although the use of biochar to promote plant growth has been reported by many researchers, the combined effect of prickly pear waste biochar (BC) and Azolla (AZ) in a field experiment on the roselle plants did yet receive attention. Therefore, the study aims to evaluate the effect of biochar and Azolla extract on the growth, production, and quality of roselle plants. The experiment treatments were in a completely randomized block design with three replicates. Biochar was added at rates of 0, 10, and 20 ton ha −1 and AZ was applied at rates of 0, 3, and 6% in addition to a control treatment. Biochar added at high rate (20 ton ha −1 ) significantly increased the fresh and dry weights of sepals by 27.98 and 35.73%, respectively, compared to the control. The corresponding values were significantly increased by 11.89 and 11.85% over the control when Azolla was added at rate of 6%. The interaction effect of both BC and AZ treatments at high rate significantly increased the fresh and dry weight of sepals by 47.16 and 60.59%, respectively, compared to the control. The interaction effect of BC and AZ realized significant effect on soil properties, growth and yield, as well as pigments of roselle plants. This is a good evident means that BC and AZ applications separately or combined are considered promising materials for sustainable organic agriculture and safety food.

Traditional, Modern, and Molecular Strategies for Improving the Efficiency of Nitrogen Use in Crops for Sustainable Agriculture: a Fresh Look at an Old Issue - Ahmed S. Elrys; Ahmed S. Elnahal; Ahmed I. Abdo; El-Sayed M. Desoky; Eman Selem; Mostafa M. Rady (Journal of Soil Science and Plant Nutrition, 2022)
Reactive nitrogen (N) plays a pivotal role in supplying N to plants and soil microbes, but it has negative environmental impacts through influencing the quality of water and air, which in turn influences human health. Thus, there is an urgent necessity to maximize N benefits while reducing the negative impacts on the environment. Improving crop N use efficiency (NUE) is required for environmental conservation and agricultural sustainability. Thus, the pivotal objective of this article is to introduce the modern developments and imminent prospects of improving crops NUE using various complementary methods. Here, the approaches of site-specific N management, use of synthetic and biological nitrification inhibitors, microbial nitrate (NO 3 − ) immobilization stimulation, and stimulation of the dissimilatory nitrate reduction to ammonium (DNRA), adopting agroforestry system, breeding techniques, quantitative trait loci (QTL) mapping, omics approaches, and potential new targets and overexpression of N-related genes were presented as effective approaches to improving NUE. Optimal rate, time, application methods, using specially formulated forms of fertilizer, and using nitrification inhibitors are the most agricultural practices linked with improving NUE. The fertilizer recommendations could be often justified across the field rather than a uniform application using spatial variability of nutrient content. Restoring soil NO 3 − retention capacity and adopting agroforestry system can also be promising ways to improve NUE. Furthermore, the use of genetic modification or the development of new cultivars that use N more efficiently is critical. In addition, omics data, including transcriptomics and metabolomics, not only advance our current understanding of N reactions but also help us move towards strategies, which are more effective in improving NUE and enhancing crop production. In conclusion, this article strongly advocates the use of integrated approaches with a private insight of genetics and agricultural management when managing N.

Hepatotoxic and Neurotoxic Potential of Iron Oxide Nanoparticles in Wistar Rats: a Biochemical and Ultrastructural Study - Mostafa Mabrouk; Ghadha Ibrahim Fouad; Sara A. M. El-Sayed; Maha Z. Rizk; Hanan H. Beherei (Biological Trace Element Research, 2022)

Correction: The use of microbial inoculants for biological control, plant growth promotion, and sustainable agriculture: A review - Ahmed S. M. Elnahal; Mohamed T. El-Saadony; Ahmed M. Saad; El-Sayed M. Desoky; Amira M. El-Tahan; Mostafa M. Rady; Synan F. AbuQamar; Khaled A. El-Tarabily (European Journal of Plant Pathology, 2022)

The use of microbial inoculants for biological control, plant growth promotion, and sustainable agriculture: A review - Ahmed S. M. Elnahal; Mohamed T. El-Saadony; Ahmed M. Saad; El-Sayed M. Desoky; Amira M. El-Tahan; Mostafa M. Rady; Synan F. AbuQamar; Khaled A. El-Tarabily (European Journal of Plant Pathology, 2022)

Synthesis of core–shell activated carbon/CaO composite from Ficus Nitida leaves, as an efficient adsorbent for removal of methylene blue - Mostafa M. Emara; Rabie Saad Farag; Mahmoud F. Mubarak; Sayed Kotb Ali (Nanotechnology for Environmental Engineering, 2020)

Full Factorial Design, Optimization, In vitro and Ex vivo Studies of Ocular Timolol-Loaded Microsponges - Radwa M. A. Abd-Elal; Ghada H. Elosaily; Shadeed Gad; El-Sayed Khafagy; Yasser Mostafa (Journal of Pharmaceutical Innovation, 2020)

Effect of Formulation Variables and Gamma Sterilization on Transcorneal Permeation and Stability of Proniosomal Gels as Ocular Platforms for Antiglaucomal Drug - Sinar Sayed; Mostafa Abdelmoteleb; Maha M. Amin; Omnia M. Khowessah (AAPS PharmSciTech, 2020)

RETRACTED ARTICLE: Testing alternatives: the use of adipose-derived mesenchymal stem cells to slow neurodegeneration in a rat model of Parkinson’s disease - Fatma Y. Meligy; Dalia A. Elgamal; Eman S. H. Abd Allah; Naglaa K. Idriss; Nagwa M. Ghandour; Ehab M. R. Bayoumy; Azza Sayed Abdelrehim Khalil; Mohamed M. El Fiky; Mostafa Elkhashab (Molecular Biology Reports, 2019)

Could curcumin ameliorate titanium dioxide nanoparticles effect on the heart? A histopathological, immunohistochemical, and genotoxic study - Eman Ahmed Alaa El-Din; Heba El-Sayed Mostafa; Mai A. Samak; Eman M. Mohamed; Dalia Abdallah El-Shafei (Environmental Science and Pollution Research, 2019)

Water quality status and pollution indices of Wadi El-Rayan lakes, El-Fayoum, Egypt - Mohamed E. Goher; El-Sayed M. Mahdy; Mohamed H. Abdo; Farida M. El Dars; Mostafa A. Korium; Aya A. S. Elsherif (Sustainable Water Resources Management, 2019)

Outdoor cultivation of the green microalga Chlorella vulgaris under stress conditions as a feedstock for biofuel - Mostafa M. El-Sheekh; Saly F. Gheda; Abo El-Khair B. El-Sayed; Atef M. Abo Shady; Mai E. El-Sheikh; Michael Schagerl (Environmental Science and Pollution Research, 2019)

Secondary metabolites from fungal endophytes of Solanum nigrum - Seham S. El-Hawary; Ahmed M. Sayed; Mostafa E. Rateb; Walid Bakeer; Sameh F. AbouZid; Rabab Mohammed (Natural Product Research, 2017)

Selectivity Improvement for Spectrofluorimetric Determination of Oseltamivir Phosphate in Human Plasma and in the Presence of Its Degradation Product - Mahmoud A. Omar; Sayed M. Derayea; Islam M. Mostafa (Journal of Fluorescence, 2017)

Synthesis and antimicrobial activity of newly synthesized 4-substituted-pyrazolo[3,4-d]pyrimidine derivatives - Ahmed M. El-Sayed; Samy M. Ibrahim; Mostafa K. Soltan; Mansour E. Abo-Kul (Medicinal Chemistry Research, 2017)

Bioactive/Natural Polymeric Scaffolds Loaded with Ciprofloxacin for Treatment of Osteomyelitis - Amany A. Mostafa; Mayyada M. H. El-Sayed; Azza A. Mahmoud; Amira M. Gamal-Eldeen (AAPS PharmSciTech, 2017)

Integration of Remote Sensing & GIS to Manage the Sustainable Development in the Nile Valley Desert Fringes of Assiut-Sohag Governorates, Upper Egypt - Mostafa kamel; El Sayed M. Abu El Ella (Journal of the Indian Society of Remote Sensing, 2016)

Phylogenetic analysis of human influenza A/H3N2 viruses isolated in 2015 in Germany indicates significant genetic divergence from vaccine strains - Ahmed Mostafa; El-Sayed M. Abdelwhab; Heiko Slanina; Mohamed A. Hussein; Irina Kuznetsova; Christian G. Schüttler; John Ziebuhr; Stephan Pleschka (Archives of Virology, 2016)

Geoelectrical and hydrogeological study to delineate the geological structures affecting the groundwater occurrence in Wadi El Khariq Basin, Northwest El Maghara, north Sinai, Egypt - Mohamed A. Khaled; Ayman M. Al Tammamy; Mostafa S. Barseem; Ahmed N. El Sayed; El Sayed A. El Abed (Arabian Journal of Geosciences, 2016)

Impact of geologic setting on the groundwater occurrence in wadis El Sanab, Hashem, and Khrega using geoelectrical methods—northwestern coast, Egypt - Mostafa S. Barseem; Ahmed N. El Sayed; Ahmed M. Youssef (Arabian Journal of Geosciences, 2014)

The impact of subsurface geological structure on the groundwater occurrence using geophysical techniques in wadi El Kallabiyyah and wadi As Sabil, East Esna, Eastern Desert, Egypt - Hosny M. Ezz El Deen; Ahmed N. El Sayed; Mostafa S. M. Barseem (Arabian Journal of Geosciences, 2014)

Neocryptolepine analogues containing N-substituted side-chains at C-11: synthesis and antischistosomicidal activity - Ibrahim El Sayed; Fatem Ramzy; Samia William; Mohamed El Bahanasawy; Mostafa M. Abd El-Sattar (Medicinal Chemistry Research, 2012)

A survey of selected essential and heavy metals in milk from different regions of Egypt using ICP-AES - Elham M. El Sayed; Ahmed M. Hamed; Sanna M. Badran; Amr A. Mostafa (Food Additives & Contaminants Part B-Surveillance, 2011)